The shared genetic risk factors between Tourette syndrome and obsessive-compulsive disorder - Khoodoruth, Mohamed Adil Shah; Ahammad, Foysal; Khan, Yasser Saeed; Mohammad, Farhan (Frontiers in Neurology, 2023)
Tourette syndrome (TS) and obsessive-compulsive disorder (OCD) are two neuropsychiatric disorders that frequently co-occur. Previous evidence suggests a shared genetic diathesis underlying the comorbidity of TS and OCD. This review aims to comprehensively summarize the current literature on the genetic factors linked with TS and its comorbidities, with a focus on OCD. Family studies, linkage analysis, cytogenetic studies, and genome-wide association studies (GWAS) have played a pivotal role in identifying common and rare genetic variants connected with TS and OCD. Although the genetic framework of TS and OCD is complex and multifactorial, several susceptibility loci and candidate genes have been identified that might play a crucial role in the pathogenesis of both disorders. Additionally, post-infectious environmental elements have also been proposed to contribute to the development of TS-OCD, although the dynamics between genetic and environmental factors is not yet fully understood. International collaborations and studies with well-defined phenotypes will be crucial in the future to further elucidate the genetic basis of TS and OCD and to develop targeted therapeutic strategies for individuals suffering from these debilitating conditions.